Gene polymorphisms of angiotensin-converting enzyme, angiotensin type 1 receptor and ⁪⁯α-adducin associated with renin angiotensin-aldosterone system in Malaysian end-stage renal disease patients - Ali, Aisyah (2012)
Genetic Polymorphisms of renin-angiotensin aldosterone system (RAAS) genes has been extensively studied in relation to the progressive renal disease, hypertension and cardiovascular disease in various populations with conflicting results. The present study sought to determine the association of Insetion/Deletion (I/D) polymorphisms of the angiotensin converting enzyme (ACE), Gly460Trp of α-adducin and A1166C of angiotensin type 1 receptor(AT1R) of RAAS genes in Malaysian end stage renal subjects. A total of 380 subjects consisted of 190 end stage renal disease (ESRD)patients and 190 unrelated healthy individuals were recruited in this study. Genotypes of RAAS gene polymorphisms were determined using mutagenically separated PCR and PCR-RFLP method. There was significant difference (p<0.05) found in age, systolic blood pressure (SBP), creatinine level, triglycerides and total cholesterol between the ESRD and control subjects. There was statistically significant differences (p<0.05) were found in I/D polymorphisms of ACE and Gly460Trp polymorphism of α-adducingene and no significant difference (p>0.05) was found in A1166C polymorphism of AT1R genes between the ESRD and control subjects. The findings of this study indicate that I/D polymorphisms of the ACE gene and Gly460Trp polymorphism of α-adducin gene are a useful marker and are likely to play a major role in determining genetic susceptibility to Malaysian ESRD subjects.